Joseph Conrad’s "An Outpost of Progress": History and the Epistemics of Fiction - McKenna, Andrew J. (Anthropoetics, 2024)
Joseph Conrad’s Heart of Darkness has been praised for its critique of European colonialism in Africa and blamed for its racial stereotypes in depicting the victims of this enterprise. Its complex narrative strategies have likewise have provoked mixed reception. Conrad’s short story, “An Outpost of Progress,” written earlier than Heart, provides a clearer and more direct depiction of Europe’s role in Africa by focusing on two feckless and idle colonial agents who mindlessly repeat the alibis for ivory extraction while all the real work is performed by the indigenous foreman. When made aware of the role of slavery in this business, their friendship deteriorates amidst mutual recriminations to a point where they are of fighting over scarce supplies. The earlier portrayal of comic doubles exhibits Conrad’s debt to Flaubert, while the denouement consists in a struggle of violent doubles that ends up with one of them shooting the other and hanging himself thereafter, an outcome portrayed in a manner that accentuates the sacrificial dynamics working through their dealings with the native population. Oppression and self-destruction, murder and suicide, are Conrad’s unambiguous emblem for the colonial scheme.